Proses Pembelajaran Pada Sekolah Dasar Negeri 101 Bengkulu Selatan - Yevin Syariski; Apriana Apriana; Fadhlurrohman Fadhlurrohman (JPT : Jurnal Pendidikan Tematik, 2024)
The research method used in this research is the observation method through interviews at SDN 101 South Bengkulu. Thus, the effectiveness of a learning process is determined by the interaction of these three components. The subjects studied were the principal, teachers and 18 class V students. The data collection techniques used were observation, interviews and documentation. The purpose of this research is to determine the importance of the teacher's role in implementing an effective learning process.